To find the inverse of the given function f(x) = 3x + 12, we need to switch the roles of x and y and solve for y.
So, start with:
y = 3x + 12
Switch x and y:
x = 3y + 12
Solve for y:
x - 12 = 3y
y = (x - 12) / 3
Therefore, the inverse function, g(x), is g(x) = (x - 12) / 3.
To show that f(x) and g(x) are inverses, we need to show that f(g(x)) = x and g(f(x)) = x.
Let's start with f(g(-2)):
f(g(-2)) = f((-2 - 12) / 3)
f(g(-2)) = f(-14 / 3)
f(g(-2)) = 3(-14 / 3) + 12
f(g(-2)) = -14 + 12
f(g(-2)) = -2
Now, let's check the other composite function:
g(f(x)):
g(f(x)) = g(3x + 12)
g(f(x)) = ((3x + 12) - 12) / 3
g(f(x)) = 3x / 3
g(f(x)) = x
Since both composite functions simplify to x, we have shown that f(x) and g(x) are inverses of each other.
The domain of the original function f(x) = 3x + 12 is all real numbers since there are no restrictions on the input x.
Enter your answer and show all the steps that you use to solve this problem in the space provided.
A function is given:
f(x)=3x+12
Determine the inverse of this function and name it g(x).
Use composite functions to show that these functions are inverses.
f(g(–2)).
Explain: What is the domain?
1 answer